Korelasi Korelasi Karakteristik Perusahaan Terhadap Financial Distress Perusahaan Sektor Properti dan Real Estate - Mutia Rachmawati; Elok Heniwati; Gita Desyana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to understand the factors that influence the level of financial distress in property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The population in this study was 87 property and real estate companies listed on the IDX. From this population, researchers selected 36 companies as samples using purposive sampling techniques. The observation period in this study was five years, so the total observation data used was 118. Data analysis in this study used multiple linear regression with the help of SPSS 26 software. The results of the study showed that liquidity had a positive and significant influence on the level of financial distress with a value t-count of 6.077 > 1.98099 t-table for property and real estate sector companies listed on the IDX for the 2018-2022 period. This means that the higher the level of company liquidity, the higher the level of financial distress experienced by the company. On the other hand, profitability and company size did not show a negative and significant influence on the level of financial distress in property and real estate sector companies listed on the IDX during the observation period.